Persepsi Guru Tentang Proses Supervisi Kepala Sekolah di SMKN 1 Payakumbuh - Nofpriyaldi Nofpriyaldi; Rifma Rifma (Jurnal Bahana Manajemen Pendidikan, 2019)
This study was based on the observations of the authors who suggested that the supervision process carried out by the principal was not well implemented. The purpose of this study was to find out how the teacher’s perceptions of the supervision process of principals in Payakumbuh 1 Vocational school, which included several aspects namely: 1) supervision planning, 2) implementation of supervision, 3) evaluation of supervision, 4) follow up supervision. This type of research is deskriptif research. The study population was all teachers in Payakumbuh 1 Vocational School as many as 102 people. While the sample is determined using the slovin formula, which is 48 people. The data collection tol is a questionnaire, which is arranged in the form of a likert scale that has been tested for validity and reliability. Data were analyzed using the average  formula (mean). The purpose of this research is to find information about Organizational Culture in vocational high school of the country District Lubuk Begalung Padang City. This is a descriptive research. The population is 137 teachers and research sample is 62 teachers that taken by proportional stratified  random sampling.The instrument of this research was a questionnaire with Likert scale models that had been tested for validity and reliability. Colected data were analyzed by using the average (mean) formula. The results of this research shown the organizational culture in vocational high school of the country District Lubuk Begalung Padang City achieve good category  with an average score 4,00.